Post-chemotherapy robotic bilateral retroperitoneal lymph node dissection using a novel single-dock technique. Issue 4 (December 2016) - Stout, Thomas; Soni, Samit; Goh, Alvin
Abstract There have been no previous reports of post-chemotherapy robotic bilateral retroperitoneal lymph node dissection (RPLND) using a single-dock technique. One deterrent of robotic RPLND is that accessing bilateral retroperitoneal spaces requires patient reposition and surgical robot redocking, therefore increasing operative time. Herein we provide the first step-by-step description of a single-dock technique for robotic bilateral RPLND in the post-chemotherapy setting. We describe port placement and technique for robot positioning to optimize access to bilateral retroperitoneal spaces with a single dock. We also demonstrate the feasibility of sparing the inferior mesenteric artery when utilizing this approach. This single-dock approach was used on two patients at our institution who had residual paracaval masses following chemotherapy for metastatic testicular cancer. Mean operative time was 6 h, and neither patient had significant blood loss or suffered from any peri-operative complications.